2016
DOI: 10.3389/fendo.2016.00140
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor β in Melanoma: From Molecular Insights to Potential Clinical Utility

Abstract: Cutaneous melanoma is an aggressive tumor; its incidence has been reported to increase fast in the past decades. Melanoma is a heterogeneous tumor, with most patients harboring mutations in the BRAF or NRAS oncogenes, leading to the overactivation of the MAPK/ERK and PI3K/Akt pathways. The current therapeutic approaches are based on therapies targeting mutated BRAF and the downstream pathway, and on monoclonal antibodies against the immune checkpoint blockade. However, treatment resistance and side effects are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 207 publications
(216 reference statements)
2
77
0
3
Order By: Relevance
“…Estrogen receptor beta (ERβ) is the predominant estrogen receptor in melanoma cells. Its expression was reported to decrease with increasing depth of invasion and progression and therefore ERβ was hypothesized to have an antitumor activity in SMM . ERβ has also been considered as a possible molecular target for melanoma treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogen receptor beta (ERβ) is the predominant estrogen receptor in melanoma cells. Its expression was reported to decrease with increasing depth of invasion and progression and therefore ERβ was hypothesized to have an antitumor activity in SMM . ERβ has also been considered as a possible molecular target for melanoma treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Its expression was reported to decrease with increasing depth of invasion and progression and therefore ERb was hypothesized to have an antitumor activity in SMM. [20][21][22] ERb has also been considered as a possible molecular target for melanoma treatment. A metaanalysis of nine randomized clinical trials comparing chemotherapy with Tamoxifen, which is an estrogen antagonist, to chemotherapy alone in metastatic SMM patients showed that chemotherapy with Tamoxifen improved overall and partial response, especially in women, but did not improve mortality in 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…1 Referring to reference allele/effect allele. 2 Adjusted for age, sex, Breslow thickness, distant/regional metastasis, ulceration and mitotic rate in Cox models of SNPs and melanoma-specific survival in MDACC study and all the tests of the proportional hazards assumption for the validated SNPs were not significant (p > 0.05). 3 Adjusted for age and sex in Harvard study.…”
Section: Independent Representative Snpsmentioning
confidence: 96%
“…1 Adjusted for age, sex, Breslow thickness, distant/regional metastasis, ulceration and mitotic rate in Cox models of SNPs and CMSS in MDACC study. 2 Adjusted for age and sex in Harvard study. 3…”
Section: <0001mentioning
confidence: 99%
See 1 more Smart Citation